The cultural influences of narrative content on consumers' perceptions of helpfulness. (May 2022) - Fu, Ning
The rapid development of text analytics enables marketers to obtain the information extracted from the narrative content in user-generated content (UGC). Recent studies have also demonstrated that people with different cultural backgrounds may express their opinions about their purchase in diverse manners. This study focuses on the impact of the narrative content of consumers' perception of helpfulness. It first identifies four contextual dimensions to propose a theoretical model, demonstrating that perceptions of helpfulness may differ in respect to the consumers' varied cultural backgrounds (e.g., individualism vs. collectivism). By using Linguistic Inquiry and Word Count (LIWC), the study empirically tests the hypotheses by analyzing 111, 857 movie reviews collected for 167 American movies released both in the United States and in China from 2013 to 2016. The results reveal that individualist consumers perceive an online review that contains more self-description and future-focus content as helpful, whereas collectivist consumers rely more on online reviews containing social description and past-focus content.